Multidisciplinary Strategies for Chronic Pain Management: Integrating Neurology, Psychiatry, and Pain Medicine for Improved Patient Outcomes - Almane, Khaled Hamad M; Al Otaibi, Rakan Barky M; Alhamlan , Bandar Tayil Fankhur; Alsharari, Khalid Mushatin Hamdan; Hamdan, Khalid Mushatin; Alsaidan, Abdulmajeed Ahmed D; Alsharari, Zaid Snyan Muslim; Alsharari, Meshal Salamah Dhuhayyan; Alsharari, Abdulrahman Hanif Musabh; Alsharari, Yousef Mahdi Ghanem; Al-Osaimi, Abdul Majeed Ali; Mahzari, Ibrahim Mohammed (Journal of Ecohumanism, 2024)
Background: Chronic pain is a complex and multifaceted condition influenced by psychological, social, and biological factors. It poses significant challenges to individuals, often leading to stigma and inadequate management. Addressing chronic pain requires a comprehensive understanding of its determinants and the integration of multidisciplinary approaches to optimize patient outcomes. Methods: This review involved a non-systematic evaluation of both foundational and contemporary literature regarding the management of chronic non-malignant pain. A literature search was conducted across various databases, including PubMed, Scopus, and MEDLINE, focusing on studies published in English from 2018 to 2023. Keywords related to chronic pain, therapeutic methodologies, and multidisciplinary care were employed. Results: Findings indicate that a biopsychosocial model significantly enhances chronic pain management by incorporating medical, psychological, and social interventions. Evidence suggests that cognitive-behavioral therapy (CBT) and psychosocial treatments are effective in alleviating chronic pain and improving patient quality of life. Furthermore, multidisciplinary care involving collaboration among healthcare providers leads to better management outcomes and reduced healthcare costs. Conclusion: The effective management of chronic pain necessitates a multidisciplinary approach that considers the diverse influences on pain perception and experience. Future research should focus on refining these integrative strategies and clarifying the roles of various healthcare professionals in chronic pain management. By adopting a holistic perspective, healthcare systems can enhance the quality of care provided to individuals suffering from chronic pain.